Predictive capacity of a genetic risk score for coronary artery disease in assessing recurrences and cardiovascular mortality among patients with myocardial infarction - Rincón, Luis Miguel; Subirana, Isaac; Pérez del Villar, Candelas; Sánchez, Pedro L.; Zamorano, José Luis; Marrugat, Jaume; Elosua, Roberto (Frontiers in Cardiovascular Medicine, 2023)
The aim of this study was to evaluate the capacity of a genetic risk score (GRS) related to coronary artery disease (CAD) but independent of classical cardiovascular risk factors to assess the risk of recurrence in patients with a first myocardial infarction. A secondary aim was to determine the predictive value of this GRS. Methods: We performed a meta-analysis of individual data from three studies: a prospective study including 75 patients aged <55 years, a prospective study including 184 patients with a mean age of 60.5 years, and a case-control study (77 cases, 160 controls) nested in a cohort of first myocardial infarction patients. A GRS including 12 genetic variants related to CAD but independent of classical cardiovascular risk factors was assembled.The outcome was a composite of cardiovascular mortality and recurrent acute coronary syndrome. Results: The GRS was associated with higher risk of recurrence (HR=1.24; 95% confidence interval: 1.04-1.47). Inclusion of the GRS in a clinical model did not increase the discrimination capacity (change in c-statistic/AUC: 0.009; 95% CI: -0.007; 0.025) but improved reclassification (continuous net reclassification index: 0.29; 95% CI: 0.08-0.51). Conclusion: A GRS related to CAD but independent of classical cardiovascular risk factors was associated with risk of recurrence in patients with a first myocardial infarction. The predictive capacity of this GRS identified a subgroup of high-risk patients that could benefit from intensive preventive strategies.